IMPROVEMENT OF MICRONETWORK ACCURACY BY INVOLVEMENT OF ADJUSTMENT WITH WEIGHT - N. Sayle, Khamis (Iraqi Journal of Civil Engineering, 2007)
ABSTRACT The rapid development in computer Technology and in the instruments used in field measurements helped to overcome the problem of accuracy improvement and accuracy assessment of high precision networks. This paper deals with solution of the use of mixed observation systems, it is an essential requirement to improve the accuracy. The study of the magnitude of the correlation of error is of great importance in the efficient performance of planning, measuring and adjusting operation of survey. This paper concludes that the use of weights for mixed observation constitutes an important part in the improvement of the accuracy of a micronetwork. Weights which are determined for mixed observation after the assessment of the standard error of unit weight for each kind of observation .